Pengembangan Media Scrapbook untuk Meningkatkan Kemampuan Menyelesaikan Soal Cerita FPB Dan Kpk Kelas IV SD - Fitriyah, Lailatul; Suryatin, Suryatin; Tisngati, Urip (Scholarly Journal of Elementary School, 2022)
This study is based on the potential and requirements of mathematics learning media in elementary schools for supporting the learning process. The research is purposed to produce a learning media such as Scrapbook to Improve Grade IV Elementary School Students' Ability to Solve Highest Common Factor (HCF) and Lowest Common Multiple (LCM) Story Problems. This research was a kind of Research and Development (R&D) which the procedure used a Borg & Gall development model that is limited to the seventh step. The subject of the research was 7 students of the 4th grade at SDN 1 Karanggede. Techniques for collecting data include questionnaires, written tests, and documentation. The study's findings are as follows: (1) Media Scrapbook was created using Borg and Gall development procedures to the seventh step; (2) Scrapbook media was declared "Very Valid" by material experts with an average of 4.46 and media experts with an average of 4.37, as well the results of the student response questionnaire assessment of 97.96% with the category of "Very good"; (3) Scrapbook media has been declared effective for improving the ability to solve HCF and LCM story problems, with an average N-Gain score of 0.8 indicating a high category and a percentage of N-Gain score of 82% indicating effectiveness.